AN ADVANCED OXIDATION PROCESS : FENTON PROCESS - Gurtekin, Engin; Sekerdag, Nusret (Pamukkale Univ, 2008)
Biological wastewater treatment is not effective treatment method if raw wastewater contains toxic and refractory organics. Advanced oxidation processes are applied before or after biological treatment for the detoxification and reclamation of this kind of wastewaters. The advanced oxidation processes are based on the formation of powerful hydroxyl radicals. Among advanced oxidation processes Fenton process is one of the most promising methods. Because application of Fenton process is simple and cost effective and also reaction occurs in a short time period. Fenton process is applied for many different proposes. In this study, Fenton process was evaluated as an advanced oxidation process in wastewater treatment.
Keywords: Wastewater; Advanced oxidation process; Fenton process